Effect of Islamic social reporting: A comparative study between Indonesia and Malaysia - Herlina Rahmawati Dewi; Ayu Nailil Kiromah (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This research aims to find out: (1) The Effect of Islamic social reporting on financial performance, (2) The Effect of Islamic social reporting on the company value, and (3) Differences in disclosure of Islamic Social Reporting in Indonesia and Malaysia. The population in this research are companies listed in Indonesia Sharia Stock Index (ISSI) and Islamic stocks in Malaysia, Suruhanja Sekuriti, during the period 2014-2017. The samples of companies were determined using purposive sampling technique. The research samples in Indonesia were 50 companies with 400 observations. While in Malaysia the research samples were 50 companies with 700 observations. Data analysis used robust regression analysis. The research results indicate that (1) There are differences in the disclosure of Islamic Social Reporting between Indonesia and Malaysia. (2) Islamic social reporting has a significant positive effect on financial performance. (3) Islamic social reporting has a significant effect on company value.